A Novel Approach to Duality of Electron - Sultan Muhammad; Miss Omama (Newest Updates in Physical Science Research Vol. 11, 2021)
I decipher the quantum duality of the electron in Young’s Double-Slit Experiment. Hypothesis intends to decode the interaction of knocked-electrons with the observer and perturbative disappearance of the interference pattern. Hypothesis is based on Bohr’s Atomic Model, and the theoretical concepts of Quantization of electron. The hypothesis proposes a universal field, similar to Higg’s field, that conserves the potential energy of electrons through interaction with knocked-electrons, utilizing phenomena of pair-production. The hypothesis provides comprehensive theoretical and mathematical solutions to possibly elaborate, in a broader context, why electrons exhibit duality and the role of the observer in Young’s Double-Slit experiment through the introduction of universal field (SM-Field). The interactions between photons and knocked-electrons have been discussed. Through using the Schrodinger wave equation (SWE), a mathematical model has been derived, that is used to explain the role of the observer, and duality of the electron by using SM-field as a supplement. The prime objective of the proposed hypothesis is to understand the dual nature of the electron by presenting a mathematical and theoretical modal not just to decode the duality of the electron but also to decode the role of the observer when measuring the position of electrons